2017
DOI: 10.1002/jor.23631
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle screw augmentation with bone cement enforced Vicryl mesh

Abstract: Achieving sufficient mechanical purchase of pedicle screws in osteoporotic or previously instrumented bone is technically and biologically challenging. Techniques using different kinds of pedicle screws or methods of cement augmentation have been used to address this challenge, but are associated with difficult revisions and complications. The purpose of this biomechanical trial was to investigate the use of biocompatible textile materials in combination with bone cement to augment pullout strength of pedicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…By injecting bone cement, the bone cement can be squeezed into the bone around the screw evenly. The bone cement can increase the contact area with the bone, improve the grip between the bone and the pedicle screw bone cement, thus enhancing the stability of the screw, improving the anti-fatigue ability of spinal fixation stage and improving the surgical treatment effect [ [29] , [30] , [31] ]. There was no difference in the complication rate between the two groups, which showed that cement-reinforced pedicle screw combined with interbody fusion was safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…By injecting bone cement, the bone cement can be squeezed into the bone around the screw evenly. The bone cement can increase the contact area with the bone, improve the grip between the bone and the pedicle screw bone cement, thus enhancing the stability of the screw, improving the anti-fatigue ability of spinal fixation stage and improving the surgical treatment effect [ [29] , [30] , [31] ]. There was no difference in the complication rate between the two groups, which showed that cement-reinforced pedicle screw combined with interbody fusion was safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…The screw extraction speed was set at 5 mm/min in accordance with the ASTM standard (Tolunay et al, 2015;Aycan et al, 2016;F543-17, A, 2017). A preload of 5N was applied to eliminate initial slack and improve alignment (Schmid et al, 2018).…”
Section: Biomechanical Experiments and Testing Protocolmentioning
confidence: 99%
“…32 As the reinforced pedicle screws do not damage the anterior wall of the spinal cone, the probability of bone cement leakage is very low, and it can effectively prevent screw loosening after internal fixation. [33][34][35] Three of the studies we included compared the safety of long and short segments by reinforced pedicle screw fixation in the treatment of Kummell disease. The current meta-analysis results showed that there was no significant difference in postoperative bone cement leakage and postoperative screw loosening between LSF and SSF.…”
Section: Efficacy and Safety Of Posterior Short-segment Fixation And ...mentioning
confidence: 99%